Short-Run Bank Portfolio Behavior: An Examination of Selected Liquid Assets: Discussion - Dince, Robert R. (Journal of Finance, 1973)
Robert R. Dince, Short-Run Bank Portfolio Behavior: An Examination of Selected Liquid Assets: Discussion, The Journal of Finance, Vol. 28, No. 2, Papers and Proceedings of the Thirty-First Annual Meeting of the American Finance Association Toronto, Canada, December 28-30, 1972 (May, 1973), pp. 541-544